Political economics of higher education finance - Rainald Borck; Martin Wimbersky (Center for Economic Studies and ifo Institute (CESifo), 2009)
We study voting over higher education finance in an economy with risk averse households who are heterogeneous in income. We compare four different systems and analyse voters' choices among them: a traditional subsidy scheme, a pure loan scheme, income contingent loans and graduate taxes. Using numerical simulations, we find that majorities for income contingent loans or graduate taxes become more likely as the income distribution gets more equal. We also perform sensitivity analyses with respect to risk aversion and the elasticity of substitution between high skilled and low skilled workers.
Keywords: H52; H42; D72; 330; voting; higher education; financing scheme; Studienfinanzierung; Hochschulfinanzierung; Vergleich; Wahlverhalten; Public Choice; Spieltheorie; Bildungsverhalten; Theorie